Activation/inactivation of the classical pathway of complement in non-lesional skin of patients with systemic lupus erythematosus. - Alahlafi, A; Wordsworth, P; Wojnarowska, F (2005)
BACKGROUND: The link between the lupus band and pathogenesis remains controversial, because immunoglobulins and complement components, including the membrane attack complex, can be found in both lesional and non-lesional skin of patients with systemic lupus erythematosus (SLE). The expression of proteins that regulate complement has not been previously investigated in the skin of patients with SLE. AIM: The aim of this study is to compare the expression of protectin (CD59), which demonstrates the activation of the classical pathway of complement, in non-lesional skin obtained from patients with SLE with its expression in normal skin. This may help us explain the link between the lupus band and pathogenesis of cutaneous lupus erythematosus. METHODS: An indirect immunofluorescence technique was performed in order to provide unequivocal evidence for the activation of complement via the classical pathway and to compare the expression of CD59 in non-lesional skin from patients with SLE with normal skin samples obtained from healthy people. RESULTS: The activation of the classical pathway of complement was demonstrated in non-lesional skin in more than 90% of SLE patients investigated in this study. Staining intensity of the complement regulatory protein CD59 was markedly increased in the majority of non-lesional skin samples obtained from patients with SLE, compared to that from normals. CONCLUSIONS: CD59 is overexpressed in non-lesional skin in which complement activation has occurred. It seems likely that an increased and continuous CD59 expression may be important for maintaining the integrity of the skin BMZ during inflammatory responses involving complement activation in SLE skin. Alahlafi A, Wordsworth P, Wojnarowska F. Activation/inactivation of the classical pathway of complement in non-lesional skin of patients with systemic lupus erythematosus.